Industrial Application Aspects of the Electrochemical Reduction of CO2 to CO in Aqueous Electrolyte. Issue 1 (15th January 2020) - Krause, Ralf; Reinisch, David; Reller, Christian; Eckert, Helmut; Hartmann, David; Taroata, Dan; Wiesner‐Fleischer, Kerstin; Bulan, Andreas; Lueken, Alexander; Schmid, Guenter
Abstract: The industrialization of the electrochemical reduction of CO2 toward CO in aqueous electrolytes has recently been started using silver‐based gas diffusion electrodes. The performance of a CO2 ‐to‐CO electrolyzer model on a 10‐cm 2 cell size is assessed with respect to operating pressure, achievable current density at faradaic efficiency of CO above 90 %, composition of gas streams and operational lifetime. Operational lifetime has exceeded 1500 h. The first scaling step to 300 cm 2 has been accomplished. The rated power of such a cell is around 300 W. Abstract : Single‐step electrochemical reduction of CO2 in aqueous media is approaching industrial applicability. The article describes its fundamental properties, an industrial applicable operation window with the combined parameter set of faradaic efficiency, current density, single pass conversion efficiency and first scaling to 300 cm 2 .